A cell-permeable tool for analysing APP intracellular domain function and manipulation of PIKfyve activity. Issue 2 (15th April 2016) - Guscott, Benjamin; Balklava, Zita; Safrany, Stephen T.; Wassmer, Thomas
Abstract : In this work we developed and validated a cell permeable tool to study the intracellular function of a central molecule in Alzheimer's disease, the amyloid precursor protein. We showed that it regulates the activity of the PIKfyve kinase complex. Abstract : The mechanisms for regulating PIKfyve complex activity are currently emerging. The PIKfyve complex, consisting of the phosphoinositide kinase PIKfyve (also known as FAB1), VAC14 and FIG4, is required for the production of phosphatidylinositol 3, 5-bisphosphate [PI(3, 5) P 2 ]. PIKfyve function is required for homoeostasis of the endo/lysosomal system and is crucially implicated in neuronal function and integrity, as loss of function mutations in the PIKfyve complex lead to neurodegeneration in mouse models and human patients. Our recent work has shown that the intracellular domain of the amyloid precursor protein (APP), a molecule central to the aetiology of Alzheimer's disease binds to VAC14 and enhances PIKfyve function. In the present study, we utilize this recent advance to create an easy-to-use tool for increasing PIKfyve activity in cells. We fused APP intracellular domain (AICD) to the HIV TAT domain, a cell-permeable peptide allowing proteins to penetrate cells. The resultant TAT–AICD fusion protein is cell permeable and triggers an increase in PI(3, 5) P 2 . Using the PI(3, 5) P 2 specific GFP-ML1Nx2 probe, we show that cell-permeable AICD alters PI(3, 5) P 2 dynamics. TAT–AICD also provides partial protection from pharmacological inhibition of PIKfyve. All three lines of evidence show that the AICD activates the PIKfyve complex in cells, a finding that is important for our understanding of the mechanism of neurodegeneration in Alzheimer's disease.